2006
DOI: 10.1177/030437540603100203
|View full text |Cite
|
Sign up to set email alerts
|

The Global Visa Regime and the Political Technologies of the International Self: Borders, Bodies, Biopolitics

Abstract: This article examines the micropolitics of the border by tracing the interface between government and individual body. In the first act of confession before the vanguard of governmental machinery, the border examination is crucial to both the operation of the global mobility regime and of sovereign power. The visa and passport systems are tickets that allow temporary and permanent membership in the community, and the border represents the limit of the community. The nascent global mobility regime through passp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
116
0
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(138 citation statements)
references
References 14 publications
0
116
0
22
Order By: Relevance
“…Put simply, technology has itself become the centerpiece of contemporary security systems (Ceyhan, 2008). As Salter (2006) notes, by imposing biometric passports on foreigners who seek entry into the United States, the US administration contributed directly to the transformation of biometrics into a global security norm (also see Ceyhan, 2008). Both institutional changes to the border agencies in Canada and the US, as well as the increasing reliance on surveillance and technological means of prescreening-which is presented as an effective means for pre-assessing risk-have dramatically changed how the border functions and is experienced by those crossing it, and have likewise dramatically altered the landscape of influential stakeholders involved in the management of the border.…”
Section: Technologization: the Emerging Biometric Bordermentioning
confidence: 99%
“…Put simply, technology has itself become the centerpiece of contemporary security systems (Ceyhan, 2008). As Salter (2006) notes, by imposing biometric passports on foreigners who seek entry into the United States, the US administration contributed directly to the transformation of biometrics into a global security norm (also see Ceyhan, 2008). Both institutional changes to the border agencies in Canada and the US, as well as the increasing reliance on surveillance and technological means of prescreening-which is presented as an effective means for pre-assessing risk-have dramatically changed how the border functions and is experienced by those crossing it, and have likewise dramatically altered the landscape of influential stakeholders involved in the management of the border.…”
Section: Technologization: the Emerging Biometric Bordermentioning
confidence: 99%
“…Schmitt (1922Schmitt ( /1985 writing in relation to the exercise of sovereign power argued that its essence was not necessarily the ability to coerce or rule, but rather, 'the monopoly to decide' . a monopoly that carries with it the power to define the exception and a monopoly which is most acutely expressed in those bordering processes that are concerned with the edges of state space (Salter 2006). On this point, Foucault (1991: 211) suggested that rather than imposing laws on people, governing had increasingly become a question of distributing things, by which he meant, 'employing tactics rather than laws, and even of using laws themselves as tactics -to arrange things in such a way that, through a certain number of means, such-and-such ends may be achieved' .…”
Section: Introductionmentioning
confidence: 99%
“…Embassies and visa procedures have become ever more important sites for the securing of the Euro-African border (see Zampagni, this volume). Along with Francesca Zampagni (this volume), this chapter takes embassies as delocalized borders where visa procedures constitute practices and performances of bordering (Bigo and Guild, 2005;Salter, 2006). Through visa interviews and related regulatory procedures, consular staff both create and secure the border.…”
mentioning
confidence: 99%